A study on the efficacy of online learning approaches in UiTMCPP by gender / Ayuni Athirah Mohd Azmi ... [et al.] - Mohd Azmi, Ayuni Athirah; Abd Malek Ridzuan, Nur Syazana; Azman, Mohamad Azpan; Idris, Nur Azimah (Unit Penerbitan JSKM, 2025)
This study examines the efficacy of online learning approaches at Universiti Teknologi MARA Cawangan Pulau Pinang (UiTMCPP), with a focus on gender-based differences in student perceptions and performance. Using a simple random sampling method, 86 students from Culinary Arts Management, Mechanical Engineering, and Electrical Engineering programs participated in an online survey. This study analyses student engagement and academic efficiency using descriptive and inferential statistical methods, including a one-sample t-test and an independent sample t-test. Findings revealed that while students generally preferred online learning because of the flexibility and accessibility, their perceptions did not meet the highest satisfaction level. The results also indicated that no statistically significant difference between male and female students regarding the perceived efficiency of online learning platforms, suggesting a similar level of adaptability across genders. The study highlights the importance of enhancing interactive features, real-time feedback mechanisms, and adaptive learning resources to optimize online education experiences.